Antiseptic mouthwash against pharyngeal Neisseria gonorrhoeae: a randomised controlled trial and an in vitro study. (20th December 2016) - Chow, Eric PF; Howden, Benjamin P; Walker, Sandra; Lee, David; Bradshaw, Catriona S; Chen, Marcus Y; Snow, Anthony; Cook, Stuart; Fehler, Glenda; Fairley, Christopher K
Abstract : Background: Gonorrhoea is increasing among men who have sex with men (MSM). We aimed to determine whether Listerine, a commercial mouthwash product, has an inhibitory effect against Neisseria gonorrhoeae in a randomised controlled trial (RCT) and an in vitro study, and therefore may be a potentially useful agent for gonorrhoea control. Methods: In vitro: a suspension of ∼10 8 colony forming units per mL (CFU/mL) of N. gonorrhoeae was added to a serial of dilutions (up to 1:32) of alcohol-containing Listerine mouthwashes (Cool Mint and Total Care) for 1 min. A 10 µL aliquot was spread over the surface of a gonococcal agar plate and the number of N. gonorrhoeae colonies present at each dilution was calculated. The phosphate buffered saline (PBS) was used as a control. RCT: we recruited MSM with pharyngeal gonorrhoea who returned for treatment at the Melbourne Sexual Health Centre between May 2015 and February 2016. Untreated men were randomised to rinse and gargle either Listerine Cool Mint or saline for 1 min. Pharyngeal swabs were taken before and after rinsing and gargling for culture of N. gonorrhoeae . The analysis included only men who were culture positive for N. gonorrhoeae before using the allocated solution on the day of recruitment. Results: In vitro: Listerine mouthwashes at dilutions of up to 1:4 for 1 min resulted in significant reduction of total N. gonorrhoeae counts but PBS has no inhibitory effect against N. gonorrhoeae . RCT: a total of 196 MSM were recruited, 58 (30%) were culture positive before using the solution. After gargling the allocated solution, men in the Listerine group were significantly less likely to be culture positive on the pharyngeal surface (52%) compared with men in the saline group (84%) (p=0.013). Conclusions: This data suggest Listerine, significantly reduces the amount of N. gonorrhoeae on the pharyngeal surface. With daily use it may increase gonococcal clearance and have important implications for prevention strategies. Trial registration number: ACTRN12615000716561 .